Managing Tourism Experiences and Image: A Public Sector Strategy for Bali’s Regional Competitiveness - Silvia Dewi, Putu Eva; Dwi Vata Hapsari, Raditha; Yulianti, Ida (Jurnal Ilmiah Administrasi Publik, 2025)
The tourism sector serves as a fundamental pillar of Indonesia's economic development. Bali, as the nation's premier tourist destination, faces critical challenges regarding negative destination image, adversely affecting its competitive positioning. This study examines the structural relationships between memorable tourism experiences (MTEs) and destination image on tourist loyalty in Bali, incorporating tourist satisfaction as a mediating variable for sustainable tourism development. Utilizing a quantitative approach with PLS-SEM analysis of 353 respondents, results demonstrate significant positive effects of both MTEs and destination image on loyalty. Theoretically, this research contributes to experiential tourism literature by identifying robust loyalty predictors. Practically, findings suggest destination managers should: (1) enhance experiential authenticity, (2) implement strategic image management, and (3) optimize satisfaction-driven engagement to maximize Bali's tourism potential. These evidence-based strategies aim to improve destination competitiveness while supporting local community welfare through sustainable tourism practices.